Ostracods (Crustacea: Ostracoda) from the floodplain of the Chi River, Mahasarakham Province, Northeast Thailand, with the first record of male Tanycypris siamensis Savatenalinton & Martens, 2009 - Savatenalinton, Sukonthip (Zootaxa, 2014)
The species diversity of ostracods in the floodplain of the Chi River basin, Mahasarakham Province, Northeast Thailand was examined in this study. Twenty-two samples were collected in the cool season (February 2010). Twenty-six species belonging to 18 genera were recorded, three of which are new to the Oriental region (Fabaeformiscandona subacuta (Yang, 1982), Ilyocypris monstrifica (Norman, 1862) and Limnocythere stationis Vávra, 1891) and one (Hemicypris ovata Sars, 1903) is a new record for Thailand. The most common species were Strandesia kraepelini (G.W. Müller, 1906) and Physocypria crenulata (Sars, 1903) occurring in 77% and 64% of the sampled localities, respectively. Additionally, males of Tanycypris siamensis Savatenalinton & Martens, 2009 were found and are here described for the first time. This discovery shows that the morphology of the hemipenis and of the Zenker organs of T. siamensis is similar to that of species in the genus Cypricercus. Additional comments on chorology and ecology of several taxa are also given.